Reações adversas associadas a esquemas de primeira linha em indivíduos iniciando a terapia antirretroviral - Jullye Campos Mendes (2017)
The sustained use of highly active antiretroviral therapy (HAART), in addition to contributing to the improvement of the quality of life and increased survival of people living with HIV/AIDS (PLHA), is associated with the occurrence of adverse reactions. The study of adverse drug reactions (ADR) at the start of HAART is important to increase knowledge about the safety profile of antiretrovirals and to provide data to support active pharmacovigilance actions in services providing HAART. The aim of this study was to evaluate the prevalence of ADR and associated factors during the use of HAART in PLHA at the beginning of treatment. This study is a cross-sectional study of the baseline characteristics of a prospective study entitled ECOART, conducted in three public referral services specialized in HIV/AIDS care in Belo Horizonte. Individuals with HIV/AIDS, aged 13 years old or more, with autonomy to answer the questionnaire and to use HAART, in addition to be using HAART for at least 15 days, were included. Socio-demographic, behavioral, clinical, treatment and service information were obtained from face-to-face interview and supplemented with information from the Information Systems of the Brazilian HIV/AIDS Program. The multivariate analysis was performed by logistic regression in SPSS software v.22. We included 399 patients, of which 341 (85.5%) had at least one ADR after HAART initiation and 72.7% reported up to five adverse reactions. Neurological reactions, such as dizziness, nightmares and insomnia, were the most frequent, with selfreported ADR being distinct according to HAART regimen used. Patients treated with dolutegravir regimens showed the highest mean quality of life in all domains. In the model for the total population, regardless of the HAART regimen, a positive association was observed between ADR and being female (OR = 3.52, CI = 1.0411.86) and using illicit drug (OR = 2.28, CI = 1.12-4.63). A negative association was found with age> 33 years (OR = 0.37, CI = 0.18-0.76), use of TDF/3TC/DTG (OR = 0.41; CI = 0.20-0.84) and the physical domain of quality of life (OR = 0.78, CI = 0.670.92). The final model restricted to patients using the single tablet regimen TDF/3TC/EFV showed a negative association with the CD4 + T lymphocyte count lower than 200 cells / mm3 (OR = 0.23, CI = 0.09-0.61) and the independence domain of quality of life (OR = 0.74, CI = 0.60-0.91). The final model restricted to TDF/3TC/DTG and to other regimens showed a negative association with the physical domain of quality of life (OR = 0.74, CI = 0.59-0.93) and (OR = 0.55, CI = 0.32-0.96), respectively. The prevalence of self-reported ADR to first-line antiretroviral regimens was high, with neurological reactions such as dizziness, nightmares and insomnia being more frequent. Patients taking TDF/3TC/EFV had a higher number of ADR, while those using TDF/3TC/DTG had a lower number of ADR, suggesting a good safety and tolerability profile.